Iconic Character of Bestiary Images in the Novels of F. Werfel and E. Canetti - Natalya Seibel; Julia Kazakova; Elena Shastina; Nailya Ziganshina (Space and Culture, India, 2020)
The anthropomorphic depiction of animals bearing allegorical meanings is the well-represented and actively demanded bestiary of world literature. It reflects the mythological thinking of writers and is an integral part of the worldview basis on which literary works are based. Bestiary images in the artistic text acquire the status of universal representative symbols. This study discusses bestiary images in novelistic works of Austrian writers, Franz Werfel (1890-1945) and Elias Canetti (1905-1994). Using the semiotic approach, the researchers define a range of images and meanings that are related to these two writers as representatives of the era of historical upheavals and individual authorial purposes that reflect the basis of the worldview of each of them. A bestiary image in a literary text can function as an iconic sign, which, on the one hand, reflects the material object in its materiality, and on the other hand, contributes to the emerging of "new", constructed by analogy, aesthetic reality. The similarity to the referent, in this case, is included in the overall system of ontological values. An iconic sign, after Ch.S. Pierce, refers to a simple sign based on the similarity to a thing and participating in the creation of symptoms of a higher order – symbols. Bestiary images in a literary text acquire the status of universal representative characters. The functioning of animal images in the text, their nomination, combinatorics, communication with the elements, time periods, and behavioural patterns are the way of the study of the philosophical foundations of the author's world picture. Canetti’s bestiary is represented by metaphorical images of a monkey, a cat, a pig, and a tortoise, which are used as a tool for analysing various psychic and psychological states of the characters of the novel "Blinding" (Die Blendung, 1931-1932). Multiple forms of anthropopathy and zoomorphism are based on the writer's attitude towards the initial "equality" of man and animal. The study of zoopoetics (the term of J. Lacan) of Werfel’s novel "Barbara, or Piety" (Barbara oder die Frömigkeit, 1929) helps to reveal the axiological foundation upon which the writer constructs his novels. The functioning of images of animals, a horse, for example, is related to the semantics of sacrifice that is rethought and acquiring new meanings in a new historical context. Composite images connecting different characteristics and associated with various natural elements are important. It is apparent that the study of the works by Werfel and Canetti, given the iconic nature of bestiary images, seems relevant to detect common patterns of development of European literature and culture of the first third of the 20th Century.